2017
DOI: 10.1175/jcli-d-16-0724.1
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Characteristics over East Asia in Early Summer: Effects of the Subtropical Jet and Lower-Tropospheric Convective Instability

Abstract: A quasi-stationary front, called the baiu front, often appears during the early-summer rainy season in East Asia (baiu in Japan). The present study examines how precipitation characteristics during the baiu season are determined by the large-scale environment, using satellite observation three-dimensional precipitation data. Emphasis is placed on the effect of subtropical jet (STJ) and lower-tropospheric convective instability (LCI). A rainband appears together with a deep moisture convergence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…According to Yokoyama et al (2017) Previous studies have shown that mid-tropospheric moisture is an important factor in the development of deep cumulus convection and its organization (e.g., Sherwood 1999;Kuang and Bretherton 2006;Takayabu et al 2010;Yokoyama et al 2017). We emphasize that the moistening of the mid-troposphere at around 650 hPa during the heavy rainfall event was caused not only by diabatically-generated ascent but by dynamically-forced ascent.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…According to Yokoyama et al (2017) Previous studies have shown that mid-tropospheric moisture is an important factor in the development of deep cumulus convection and its organization (e.g., Sherwood 1999;Kuang and Bretherton 2006;Takayabu et al 2010;Yokoyama et al 2017). We emphasize that the moistening of the mid-troposphere at around 650 hPa during the heavy rainfall event was caused not only by diabatically-generated ascent but by dynamically-forced ascent.…”
Section: Discussionmentioning
confidence: 88%
“…This is also consistent with Nie and Fan (2019)'s study on extreme rainfall events in the dynamical forcing-diabatic feedback perspective. Yokoyama et al (2017) showed that in the baiu season, the subtropical jet has an effect on moistening of the mid-troposphere owing to dynamically-forced ascent to the south of the subtropical jet, especially around the jet entrance, producing environments favorable for the organization of rainfall. In the heavy rainfall event in July 2018, the subtropical jet accelerated on the front of the upper-tropospheric trough (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations